2003
DOI: 10.1002/jat.904
|View full text |Cite
|
Sign up to set email alerts
|

Genistein treatment protects mice from ionizing radiation injury

Abstract: The radioprotective and behavioral effects of an acute administration of the isoflavone genistein (4',5,7-trihydroxyflavone) were investigated in adult CD2F1 male mice. Mice were administered a single subcutaneous (s.c.) dose of genistein either 24 h or 1 h before a lethal dose of gamma radiation (9.5-Gy of cobalt-60 at 0.6 Gy min(-1)). Mice received saline, PEG-400 vehicle or genistein at 3.125, 6.25, 12.5, 25, 50, 100, 200, or 400 mg kg(-1) body weight. For mice treated 24 h before irradiation there was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 30 publications
3
108
0
1
Order By: Relevance
“…Genistein has been reported to reduce acute lung injury from inflammation after lipopolysaccharide treatment [142,144]. Genistein has also been used as a radioprotector and has been shown to increase survival following whole body irradiation [145]. In addition to radioprotection studies, genistein has been investigated as an anti-cancer therapeutic [146].…”
Section: Protection Against Radiation-induced Lung Damage By Genisteinmentioning
confidence: 99%
“…Genistein has been reported to reduce acute lung injury from inflammation after lipopolysaccharide treatment [142,144]. Genistein has also been used as a radioprotector and has been shown to increase survival following whole body irradiation [145]. In addition to radioprotection studies, genistein has been investigated as an anti-cancer therapeutic [146].…”
Section: Protection Against Radiation-induced Lung Damage By Genisteinmentioning
confidence: 99%
“…One study demonstrated that administration of genistein (6) resulted in alleviation of the lethal effects of radiation exposure in mice without changes in behavior, body weight or histopathology. In that investigation, genistein (6) was shown to be radioprotective when administered 24 h prior to γ-irradiation (9.5 Gy), but was not effective when administered 1 hr prior to irradiation, possibly due to the antioxidant properties and immuno-stimulatory activity of genistein (6) (Landauer et al, 2003). Genistein (6) treatment resulted in reduced expression of inflammatory cytokines including TNF-α, IL-1β, and TGF-β and resulted in a reduction of oxidative stress and protection against DNA damage in lungs of rats after irradiation (Calveley et al, 2010).…”
Section: Genisteinmentioning
confidence: 99%
“…Indeed, curcumin (4) induced significant inhibition of IRinduced NF-κB activation in neuroblastoma cells, SK-N-MC and SH-SY5Y, resulting in suppression of NF-κB-mediated transcription, such as hTERT mRNA, which is essential for activation of telomerase (Aravindan et al, 2011). In addition, curcumin (4) also induced suppression of many NF-κB-regulated gene products including cyclin D1, c-myc, Bcl-2, Bcl-xL, cellular inhibitor of apoptosis protein-1, cyclooxygenase-2, matrix metalloproteinase-9, and vascular endothelial growth factor, which could be induced by radiation therapy and mediate radioresistance (Kunnumakkara et al, 2008 Landauer, et al, 2003;Calveley et al, 2010 Cell cycle arrest, Inhibition of AKT activation 0-100 μM; 5 mg/day p.o. ; Hillman et al, 2001;Hillman et al, 2004;Yashar et al, 2005;Raffoul et al, 2006;Zhang et al, 2006;Hillman et al, 2007 Quercetin (7) Antioxidant activity et al, 2010 --i.g., intragastrically; i.p., intraperitoneally; i.v., intravenously; p.o., orally; s.c., subcutaneously administered.…”
Section: Curcuminmentioning
confidence: 99%
“…BIO300 LANDAUER et al have investigated the radioprotective and behavioral effects of an acute administration of the iso avone genistein (4', 5, 7-trihydroxy avone) using the mouse model. 52) The mice were administered a single subcutaneous (s. c.) dose of genistein either 24 h or 1 h before a lethal dose of gamma radiation (9.5 Gy of cobalt-60 at 0.6 Gy min -1 ). They demonstrated that a single s. c. administration of the avonoid genistein at non-toxic doses, 25 to 400 mg kg -1 , revealed 60 to 88% survival in irradiated mice.…”
Section: )mentioning
confidence: 99%